Liquid communication: how FC Barcelona is spreading Sentiment Blaugrana one drop at a time - Zapata, Andrea D. Dájer, author; Diffrient, David Scott, advisor; Williams, Elizabeth, committee member; Pedrós-Gascón, Antonio Francisco, committee member (Colorado State University. Libraries, 2013)
This thesis explores the digital strategy of the Catalan sports club FC Barcelona. The club has gained global popularity in the last several years due to its success in league and international competitions. FC Barcelona's digital strategy has created a communicative network that allows for the establishment of a global community of fans. Within this strategy, a new form of communication between organizations and a worldwide audience has developed, one that I call "liquid communication." This term refers to a type of communication that can easily go back and forth between the participants involved. It is communication that is neither restricted by time or space, nor dictated by any type of social status. Liquid communication is needed in the new globalized arena where the Internet and social networks are frequently employed, because it is able to fully capture and analyze the bivalent flows of information, feedback and messages that are being deployed throughout the world into a single communicative channel. Taking Paul M. Pederson, Kimberly S. Miloch, and Pamela C. Laucella's Strategic Sports Communication Model as a source of inspiration, I propose a new, more dynamic and up-to-date communication model that can be adapted to different types of organizations and which takes into account the new technologies that have emerged in recent years.
Keywords: communication; social media; globalization; FC Barcelona